PENGEMBANGAN PENDIDIKAN AGAMA ISLAM SEBAGAI BUDAYA SEKOLAH - Muhammad Munif (PEDAGOGIK : JURNAL PENDIDIKAN, 2016)
This paper illustrates the importance of the development of Islamic Reli- gious Education (PAI) into the school culture. Strategies to realize it can be done in several ways; (1) Power strategy, (2) persuasive strategy, and (3) normative re-educative. Habituation be important to support the de- velopment efforts of PAI into a religious culture in schools, because ha- bituation is the result of a process of continuous exercise to be a religious culture in the school that will have positive implications towards the reali- zation of the purpose PAI, which is to realize human religious and noble, the man who was knowledgeable, diligent worship, intelligent, productive, honest, fair, ethical, disciplined, tolerant (tasamuh), maintaining harmony in personal and social development and developing a culture of religion in the school community. Implementation of religious culture in schools as well as solutions to the problems of PAI related to the lack of hours of les- sons and practices of learning that only pay attention to cognitive aspects alone and ignore the development aspects of affective and conative-volitif, the will and determination to practice the values of religious teachings in everyday life.